Efektivitas Hipnoterapi dalam Manajemen Nyeri pada Gangguan Muskuloskeletal - Ramadhan, Syahru; Irawati, Dewi; Maria, Riri; Arista, Liya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of hypnotherapy on pain management in patients with musculoskeletal disorders. The research method used was a systematic review carried out by searching for literature articles using Google Web, namely PubMed, Embraced, Science Direct, and ProQuest. The keywords used in this systematic review are musculoskeletal diseases, hypnotherapy or hypnosis, and pain. Inclusion criteria are male and female gender, adult age, year of publication in the last 10 years (2013-2023), and English language. The research results showed that a search of 402 articles was found, and only 5 articles were selected where hypnotherapy was effective in reducing pain in patients experiencing musculoskeletal problems such as fibromyalgia, chronic nonspecific low back pain, burns, and chronic brachial neuralgia. In conclusion, hypnotherapy can reduce pain in musculoskeletal disorders. Keywords: Hypnotherapy, Musculoskeletal, Pain.